أهم المتغيرات الاقتصادية و الاجتماعية و الديموغرافية المؤثرة في معدل الخصوبة الكلي في مجموعة الدول الإسلامية (دراسة تطبيقية من بيانات تقرير التنمية البشرية الصادر من الأمم المتحدة للعام 2014م) - احمد, عادل علي; بله, محمد أحمد (Gezira Journal of Economic and Social Sciences; مجلد 6 عدد 2 (2015), 2015)
The aim of this study is to identify the most important socio-economic and demographic factors affecting the total fertility rate of women throughout the duration of fertilization for the age group (49-15) years on the level of Islamic countries ,the study covered data of (57) Islamic countries included in the Human Development Report 2014, the multiple linear regression method used in the selection of the most important and significant factors affecting the dependent variable total fertility rate in Islamic countries group.Thiss tudy has concluded the following results: Significane of the population less than 15 years as percentage of total population,life expectancy at birth and mortality rates under 5 age (per 1,000 live births)as the most important demographic variables and associated with a positive correlation on the total fertility rate.Moreover the significance of the gross national income percapita variableas one of the economic variables and results a positive correlation with the total fertility rate.Significant of the adults literacy rates and gross secondary enrolment ratios as ones of social variables and associated with anegative correlationto total fertility rate.The study recommended that the necessity of adopting vital registration systems to be more comprehensive and accurate in Islamic countries and the need for applythe modern scientific techniques in weighting and correcting data.